CONTEMPORARY VIRUS THREATS FOR WINDOWS OPERATING SYSTEMS FAMILY - Пархоменко, І.; Молодан, Б. (Science-based technologies, 2011)
Considered the most technologically and dangerous virus threats in 2010 year, their principles of work, internal architecture, vulnerability used malware and methods for circumventing anti-virus protection software.